Carbapenem Treatment and Outcomes Among Patients With Culture-Positive Complicated Intra-abdominal Infections in US Hospitals: A Retrospective Cohort Study. (25th November 2019) - Zilberberg, Marya D; Nathanson, Brian H; Ditch, Kristen; Lawrence, Kenneth; Olesky, Melanie; Shorr, Andrew F
Abstract: Background: Carbapenems are a frequent firstline therapy in complicated intra-abdominal infections (cIAIs). We examined the microbiology, epidemiology, and outcomes among patients hospitalized in the United States with culture-positive cIAIs in the context of their exposure to empiric carbapenem treatment (ECT). Methods: We performed a multicenter retrospective cohort study of Premier database of ~180 hospitals, 2013–2017. Using an International Classification of Diseases (ICD)-9/10-based algorithm, we identified all culture-positive adult patients hospitalized with cIAI and examined their microbiology, epidemiology, and outcomes. Results: Among 4453 patients with cIAIs, 3771 (84.7%) had a gram-negative (GN) and 1782 (40.0%) a gram-positive organism; 1185 (26.6%) received ECT. Compared with those on non-ECT, patients on ECT were less frequently admitted from home (82.5% vs 86.0%) or emergently (76.0% vs 81.4%; P < .05 for each); E. coli were less frequent, whereas P. aeruginosa and Enterococcus spp. were more prevalent and resistance to third-generation cephalosporins (C3R; 10.1% vs 5.1%; P < .001) and carbapenems (CR; 3.6% vs 1.2%; P < .001) was more common. In adjusted analyses, ECT was associated with no rise in mortality, shorter postinfection length of stay (–0.59 days; 95% confidence interval [CI], –1.15 to –0.03), but higher postinfection costs ($3844; 95% CI, $1921 to $5767) and risk of Clostridioides difficile (odds ratio, 2.15; 95% CI, 1.02 to 4.50). Conclusions: Among patients hospitalized with cIAI, the majority were gram-negative. Despite a 10% prevalence of C3R, fully one-quarter of all empiric regimens contained a carbapenem. ECT was a marker for slightly lower postinfection length of stay, but higher costs and risk of hospital complications.